INDILACT – Extended voluntary waiting period in primiparous dairy cows. Part 1: randomized controlled trial – Daily milk yield - Edvardsson Rasmussen, Anna (Swedish University of Agricultural Sciences, 2022)
The objective of the study is to investigate how an extended voluntary waiting period between calving and first insemination in primiparous cows would affect milk production and fertility during their first and second calving interval.
The data is registered between August 2018 to September 2021.
Data from 2 different sources. Access to these data is restricted due to the agreement with the principal owner of the data Växa Sverige.
1. Data (.txt files) from the Swedish Official Milk Recording System, operated by Växa Sverige regarding breed, calvings, inseminations, 305-d lactation yields, test-day yields, and dry-off dates from 16 farms. The inclusion criteria for the farms included herds with >100 dairy cows in production and a herd average milk production of at least 9 000 kg ECM/cow/year, a mean CI of < 14 months, and a system for daily milk yield registration.
2. Daily milk yields from the milking systems on the farms (three different types of systems: DeLaval, Lely and GEA), Excel files.
Metadata available:
One file with metadata, describing the data processing steps for each category of data, is provided. Also available are Code-lists for reading the data from the text files and for decoding the codes in the text files. R scripts with statistical calculations are also available.
Daily milk yields from the milking systems on the farms (three different types of systems: DeLaval, Lely, and GEA), Excel and CSV files. The majority of data is available, but there are holes with lacking information due to files not being sent from the farms before they were deleted from the milking systems.
Variables Farm-ID, cow-ID, date and time for milking, milk yield per milking (kg).

Studien syftar till att undersöka hur en förlängd frivillig väntetid mellan kalvning och första insemination påverkar mjölkproduktion och fertilitet för förstakalvare under deras första och andra kalvningsintervall.
Data registrerades mellan augusti 2018 och september 2021.
Det finns data från två olika källor. Tillgången till dessa data är begränsad på grund av avtal med ägaren av data (Växa Sverige).
1. Data (.txt filer) från Kokontrollen som sköts av Växa Sverige gällande ras, kalvningar, inseminationer, 305-dagarsavkastning, provmjölkningar och sindatum från 16 gårdar. Inklusionskrieterier för gårdarna var > 100 kor i produktion, samt medelavkastning på minst 9 000 kg ECM/ko och år, medel KI på < 14 månader samt att de skulle ha ett system för daglig mjölkmängdsregistrering.
2. Excelfiler med data från gårdarnas egna mjölkningssystem (DeLaval, Lely och GEA) med dagliga mjölkmängder (från tre olika system: DeLaval, Lely och GEA).
Metadata (tillgängligt):
En metadatafil för respektive kategori av data har skapats med beskrivning av databearbetningen. Dessutom finns kodnycklar för hur koderna i textfilerna ska läsas ut samt kodlista för koder som använts i textfilerna. R-skript med statistisk analys finns också tillgängliga.
Excel- och CSV-filer med data från gårdarnas egna mjölkningssystem (DeLaval, Lely och GEA) gällande dagliga mjölkmängder, Excel och CSV filer. Majoriteten av data från gårdarna finns tillgänglig, men det finns hål i datainsamlingen om filerna från gårdarna inte skickats i tid innan de raderats från gårdarnas system.
Variabler: GårdsID, ko-ID, datum samt tid vid mjölkning, mjölkmängd per mjölkning (kg).
INDILACT – Förlängd frivillig väntetid för förstakalvare. Del 1: randomiserad kontrollerad studie – Dagliga mjölkmängder
INDILACT - Part 1
Keywords: milk production; dairy cattle; dairy cow; dairy farm; lactation; laktation; extended; förlängd; extended lactation; förlängd laktation; calving interval; kalvningsintervall; voluntary waiting period; frivillig väntetid; extended calving interval; förlängt kalvningsintervall; extended voluntary waiting period; förlängd frivillig väntetid; cow; ko; lactation yield; laktationsavkastning; Animal and Dairy Science; Husdjursvetenskap